2018
DOI: 10.1007/s10107-018-1288-y
|View full text |Cite
|
Sign up to set email alerts
|

Least cost influence propagation in (social) networks

Abstract: Influence maximization problems aim to identify key players in (social) networks and are typically motivated from viral marketing. In this work, we introduce and study the Generalized Least Cost Influence Problem (GLCIP) that generalizes many previously considered problem variants and allows to overcome some of their limitations. A formulation that is based on the concept of activation functions is proposed together with strengthening inequalities. Exact and heuristic solution methods are developed and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
29

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 24 publications
1
29
0
29
Order By: Relevance
“…When that is not the case, the formulation must add binary variables (one for each node) to keep track of the set of activated nodes at the end of the influence propagation process and embed the TU based integer programming formulation onto the subgraph defined by these activated nodes. In this regard, the recent paper by Fischetti et al [7] takes a big first step.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When that is not the case, the formulation must add binary variables (one for each node) to keep track of the set of activated nodes at the end of the influence propagation process and embed the TU based integer programming formulation onto the subgraph defined by these activated nodes. In this regard, the recent paper by Fischetti et al [7] takes a big first step.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to an earlier (working) version of our paper, Fischetti et al [7] considered the LCIP in a general setting where neighbors of a node may exert unequal influence, the entire network need not be influenced (i.e., 0 < ≤ 1), and the influence structure can be nonlinear. They proposed a novel set covering based formulation for this version of the LCIP.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been observed that interest in researching and solving optimization problems related to the propagation of influence in social networks has increased 205,206 . Most of these problems are related to the identification of key players in the social network, which has critical importance for the process of influence propagation 207 . Although most of the current studies assume the well‐known propagation rates, scenarios in which the rates may increase dynamically for popular subjects are still a big challenge 208 …”
Section: Future Trendsmentioning
confidence: 99%